Time for school, little blue truck - Schertle, Alice (Houghton Mifflin Harcourt, 2021)
"Ride along to school with the #1 New York Times best-selling Little Blue Truck and meet Blue's new friend: a bright yellow school bus. Beep-beep! Little Blue Truck and his good friend Toad are excited to meet a bright yellow school bus on the road. They see all the little animals lined up in the school bus's many windows, and Blue wishes he could be a school bus too. What a fun job--but much too big for a little pickup like Blue. Or is it? When somebody misses the bus, it's up to Blue to get his friend to school on time. Beep! Beep! Vroom!"--Publisher description.